Development of a High Oleic Cardoon Cell Culture Platform by SAD Overexpression and RNAi-Mediated FAD2.2 Silencing - Cappetta, Elisa; De Palma, Monica; D’Alessandro, Rosa; Aiello, Alessandra; Romano, Raffaele; Graziani, Giulia; Ritieni, Alberto; Paolo, Dario; Locatelli, Franca; Sparvoli, Francesca; Docimo, Teresa; Tucci, Marina (Frontiers in Plant Science, 2022)
The development of effective tools for sustainable supply of phyto-ingredients and natural substances with reduced environmental footprints can help mitigate the dramatic scenario of climate change. Plant cell cultures-based biorefineries can be a technological advancement to face this challenge and offer a potentially unlimited availability of natural substances, in a standardized composition and devoid of the seasonal variability of cultivated plants. Monounsaturated (MUFA) fatty acids are attracting considerable attention as supplements for biodegradable plastics, bio-additives for the cosmetic industry, and bio-lubricants. Cardoon (Cynara cardunculus L. var. altilis) callus cultures accumulate fatty acids and polyphenols and are therefore suitable for large-scale production of biochemicals and valuable compounds, as well as biofuel precursors. With the aim of boosting their potential uses, we designed a biotechnological approach to increase oleic acid content through Agrobacterium tumefaciens-mediated metabolic engineering. Bioinformatic data mining in the C. cardunculus transcriptome allowed the selection and molecular characterization of SAD (Stearic acid desaturase) and FAD2.2 (fatty acid desaturase) genes, coding for, key enzymes in oleic and linoleic acid formation, as targets for metabolic engineering. Twenty-two and twenty-seven fast-growing independent CcSAD overexpressing (OE) and CcFAD2.2 RNAi knocked out (KO) transgenic lines were obtained. Further characterization of five independent transgenic lines for each construct demonstrated that, successfully, SAD overexpression increased linoleic acid content, e.g. to 42.5% in the CcSADOE6 line compared with 30.4% in the wild type (WT), whereas FAD2.2 silencing reduced linoleic acid in favor of accumulation of its precursor, oleic acid, e.g. to almost 57% in the CcFAD2.2KO2 line respect to 17.7% in the WT. Moreover, CcSADOE6 and CcFAD2.2KO2 were also characterized by a significant increase in total polyphenolic content up to about 4.7 and 4.1 mg g-1 DW as compared to 2.7 mg g-1 DW in the WT, mainly due to accumulation of dicaffeoyl quinic and feruoyl quinic acids. These results pose the basis for the effective creation of an engineered cardoon cells-based biorefinery accumulating high levels of valuable compounds from primary and specialized metabolism to meet the industrial demand for renewable and sustainable sources of innovative bioproducts.